Un narrador sobre el caballo de la calesita - Graciela Villanueva (Cuadernos LIRICO)
With the conviction that the opening and closing lines of a text, especially in literary fiction, are privileged places of intertextual flow and exchange between words and world, this paper analyses the forms of continuity and the expression of origin on the threshold of Saer’s narrative fiction. Manuscript analysis confirms the importance of incipits and excipits as an expression of a writing project in perpetual motion.